(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Inflammation and pain are the most common health problems treated with traditional remedies which mainly comprise medicinal plants. A number of natural products are used in the traditional medical systems in many countries. An alternative medicine for the treatment of various diseases is getting more popular. Many medicinal plants provide relief of symptoms comparable to that of obtained from allopathic medicines. Therefore agents of natural origin with very little side effects are required as substitute chemicals therapeutics. The Ayurvedic preparations include Rheumartho and Rheumatil (150µg/ml, 300µg/ml, and 450µg/ml)was investigated for anti-inflammatory effects in Invitro Method. Human red blood cells membrane stabilization method and inhibition of albumin denaturation was adopted for the in-vitro anti-inflammatory activity. The ayurvedic drugs were effective in inhibiting the heat induced haemolysis at different concentrations. The results showed that Rheumatil and Rheumartho at concentration 150 µg/ml, 300µg/ml protect significantly (P<0.01) the Erythrocyte membrane against lysis induced by heat.It was concluded thatAyurvedic preparations (Rheumartho and Rheumatil)possess anti-inflammatory with lesser side effects and more beneficial effects.